Avances en la obtención de variedades de yuca (Manihot esculenta Crantz) con alta calidad de almidón mediante mutación inducida - Rosero, Elvia Amparo; Ceballos, H.; Fregene, Martin A.; Tofiño Rivera, Adriana Patricia; Morante, N; Pérez Velásquez, Juan Carlos; Castelblanco, W.H. (2007)
The cassava starch presents a little variation in its quality. Although induced mutations are a source of inherited variation for desirable traits, phenotypic expression of mutants is currently difficult to detect due to its heterozygous condition. The objective of this work was to produce M2 populations in order to increase the homozygous level of traits related to starch quality and the phenotypic characterization of irradiated plants (M1) to evaluate the induced variability. Botanical seeds from families CM9331, SM3015, SM3045, GM155, C4, and C127 were irradiated with gamma rays and fast neutrons. Plants were established in an experimental plot in the Research Station of Corpoica-Palmira. Self-pollination was carried out both to eliminate the possible chimerical states as well as to increase the level of homozygosity. In order to identify chimeras and/or useful traits among treatments, a morphological screening were made using 9 quantitative and 18 qualitative parameters. A total of 9707 flowers were self-pollinated. The percentage of surviving plants was 60% and 29% for seeds treated with gamma rays and fast neutrons, respectively. Quantitative descriptors revealed high variability. The main components analysis suggested formation of groups related to ramification and vigor. For qualitative description, chimerical plants in crust color of stem and leaf shape, and remarkable effects on the flower type (e.g., hermaphrodite flower and apomictic behavior) were observed. The multiple correspondence analysis suggested clusters related to the flowering. These results demonstrate the effect of the radiation sources on the phenotypic variability of the population. Future analysis of segregating populations will allow detection of useful variability for traits related with starch quality.